Markers of Subclinical Cardiovascular Disease in Nonfunctional Adrenal Incidentaloma Patients without Traditional Cardiovascular Risk Factors - Cansu, Güven Barış; Sarı, Ramazan; Yılmaz, Nusret; Özdem, Sebahat; Çubuk, Metin (Experimental and Clinical Endocrinology & Diabetes, 2017)
Introduction: Data regarding cardiovascular risk in patients with non-functional adrenal incidentaloma (NFAI) are limited. The objectives of this study are to investigate markers of subclinical cardiovascular disease like carotid intima media thickness (CIMT), pulse wave velocity (PWV), augmentation index (AIx), soluble CD40 ligand (sCD40L) and leptin levels in NFAI patients without traditional cardiovascular risk factors and healthy control group.Methods: This study involved 35 patients with NFAI (11 males, 24 females; mean age, 52.4±7.7 years) and 35 healthy subjects as control group (11 males, 24 females; mean age, 51.8±7.2 years). CIMT was evaluated by ultrasonographical methods. PWV and AIx were measured with TensioClinic arteriograph system. Serum leptin and sCD40L levels were measured by ELISA.Results: In NFAI patients group; CIMT (p<0.001), PWV (p<0.001), AIx brachial (p<0.001) and AIx aorta (p=0.008) were found higher than the control group. Cortisol levels after 1mg dexamethasone suppression test (DST) were higher (p=0.006) and DHEASO4 levels were lower (p=0.008) in NFAI patients than control group. We found that CIMT had positive correlation with age (r=0.484, p<0.005), triglycerides (r=0.378, p<0.005) and cortisol level after 1 mg DST (r=0.346, p<0.005); PWV had positive correlation with total cholesterol (r=0.338, p<0.005) triglycerides (r=0.335, p<0.05) and insulin levels (r=0.426, p<0.005); AIx brachial had a positive correlation with triglycerides (r=0414, p<0.05) and negative correlation with DHEASO4 (r=−0.380, p<0.005); leptin levels had a positive correlation with body mass index (r=0.541, p<0.001) and HOMA-IR index.Conclusion: We showed that subjects with NFAI without traditional cardiovascular risk factors featured several disturbances (CIMT, PWV and AIx) compared to the control group that could be attributable to increased cardiovascular risk.
Keywords: non-functional adrenal incidentaloma; carotid intima media thickness; pulse wave velocity; soluble CD40 ligand; leptin